Genome-wide dissection of AT-hook motif nuclear-localized gene family and their expression profiling for drought and salt stress in rice (Oryza sativa) - Ambadas, Dhanorkar A.; Singh, Ashutosh; Jha, Ratnesh Kumar; Chauhan, Divya; B., Santhosh; Sharma, Vinay Kumar (Frontiers in Plant Science, 2023)
AHL (AT-hook motif nuclear localized) genes are functionally very less explored but their nature is very diverse. In the present study, we identified 20 AHL genes in rice. Phylogenetic analyses and evolutionary classification of AHL genes showed that they are conserved in plants but the number of genes is still expanding in different crops and regulating new biological functions. Gene structure analysis showed that OsAHLs have with and without introns types of genes suggesting that the AHL genes added intron during evolution for neofunctionalization. The cis analysis of OsAHL genes suggested its motif diversity. In order to understand the function, 19 transcriptomes were identified from various tissues and different developmental stages of rice and it was divided into 8 groups by different temporal and spatial expression. Through co-expression analysis, 11 OsAHLs and 13 novel genes with intricate networks that control many biological pathways in rice were identified. The interactions of OsAHL proteins showed that they co-regulate important processes including flowering, reproductive organ development, photosynthesis activity, etc. The functionality of all 20 genes of OsAHL for drought and salt stress in leaf tissues of two contrasting genotypes (IR64 and NL44) of rice was studied by qRT-PCR. The result clearly showed significant upregulation of OsAHL genes under drought and salt conditions over the control. The differential expression between IR64 and NL44 showed significantly upregulation of OsAHL genes in NL44 as compared to the IR64 genotype under drought and salt stress. Overall, the result indicates that AHL genes might be involved in mediating drought and salt-signaling transduction pathways. The drought and salt tolerance nature of NL44 was also confirmed by expression profiling.